ESTUDIO ICONOLÓGICO E ICONOGRÁFICO DE LA REPRESENTACIÓN ESCULTÓRICA DE FERNANDO DAQUILEMA REALIZADA EN LA FACULTAD DE CIENCIAS DE LA EDUCACIÓN HUMANAS Y TECNOLOGÍAS PERÍODO OCTUBRE 2019 – MARZO 2020 - Carpio Arias, María Natalia (2020)
Fernando Daquilema is a representative of the memory of indigenous peoples and their vindication. This research aimed at the iconographic and iconographic study of its sculptural representation, carried out at the Faculty of Education, Human Sciences and Technologies, in the Aesthetic Culture career. A bibliographic study on aesthetic culture, art and the historical context of Fernando Daquilema was made. In the methodological section, an analysis was made in its three moments: pre iconographic, iconographic and iconographic. Thus, it was concluded that there are approaches that have to do with the historical, essay and academic aspects of the figure of Fernando Daquilema. From the sculptural representation, its creation focused on the face that represents the claim and is an extension of the distinctive features of the indigenous people and the community of Cacha, the experimentation that was carried out thanks to the educational support and especially the use of Silicone Artesil 1, which allows the work to be reproduced as many times as required. As a result, 1 and a half meter of 120 mm thick fiberglass was used, which is a medium standard, resulting in an 85 cm sculpture with a base 37 cm wide and 47 cm on the shoulder part, This material is recommended, as it was found that a mold is obtained that will serve for future replicas of the same sculpture.